Application of Decation Media (Location Plan) to Improve Understanding of Location and Direction in Grade 1 Elementary School Students - Sunaisah, Sunaisah; Maulida, Farida; Maharani, Fara Fatika; Astuti, Nur Kusuma; Pratiwi, Ika Ari (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to develop and test the feasibility and effectiveness of DEKASI (Location Plan) learning media to improve understanding of location and direction in grade 1 elementary school students. The background of this study comes from the need for concrete and fun learning media so that students can understand the concept of space visually. The phenomenon raised in this study is the low understanding of students regarding the direction and position of objects in space. This study has an element of novelty in the development of interactive media based on location plans, presented in an interesting and easy-to-understand manner by students in early grades. Research Methods: This study uses a descriptive method with a qualitative and quantitative approach, involving a validation process by experts and limited trials on grade 1 elementary school students. The instruments used in the study were validation sheets and student response questionnaires. Finding/Results: The validation results showed that this media was very feasible to use (90% feasibility), while student responses showed high enthusiasm and ease of understanding of the concept of direction and location. Conclusion: The conclusion of this study is that DEKASI media is effective and interesting to use in learning the topic of location and direction in grade 1 elementary school. The implication of this study is the need for integration of visual and interactive media in basic learning to improve students' spatial understanding.